Effects of hydroxyapatite associated to collagen type I graft in bone repair of critical defects in rabbits - Bertoli , Fernanda Mara de Paiva (2022)
The aim of this investigation was to evaluate the influences of a malleable bone graft composed by hydroxyapatite and collagen type I in bone formation. Three surgical sites of critical size were prepared in twelve rabbits’ calvarias. The control defect was fulfilled with blood clot and the experimental defects were fulfilled with the graft. The euthanasia occurred in three times: 4, 8 and 12 weeks after the surgical procedures. The specimens were analyzed in light, fluorescence and scanning electronic microscopes. The quantitative evaluation was made by histomorphometric analysis, in order to calculate the percentage of new bone formed and the area of the hydroxyapatite particles. The results were submitted to two way ANOVA test and Tukey`s post hoc. New bone formation was accelerated in early stages of the healing process. It was seen more intensive bone formation in the periosteum side than in the dura mater membrane side in all groups. Besides that, in experimental sides the new bone was surrounding the hydroxyapatite particles with minimal amount of inflammatory cells, which confirmed the biocompatibility and osteoconduction properties of this material. Besides that, the hydroxyapatite particles showed gradual and progressive absorption at the same time that the bone was being formed.